Mitigating Risks in Cloud Accounting: Strategies and Implications for Financial Institutions - Anwaar, Dr.Saiqa; Ms.Remissa (UMT Artificial Intelligence Review, 2025)
This study investigates the impact of cloud accounting technology on businesses in Pakistan with a focus on the banking sector. As technological advancement accelerates, cloud accounting has become essential to maintain competitiveness. The current research aims to explore the adoption, benefits, challenges, and risks associated with cloud-based accounting systems. A deductive methodology was used. Data was collected from 200 experienced bank employees through questionnaire. A cross-sectional analysis was conducted to examine key variables, such as relative advantage, complexity, and compatibility. Quantitative analysis techniques were applied to identify the patterns and relationships. The findings revealed that while cloud accounting offers significant benefits—such as cost efficiency, scalability, and operational flexibility—it also introduces new risks, including data security breaches and compliance concerns. The study proposes effective risk mitigation strategies, including strong encryption protocols, continuous system monitoring, and rigorous vendor vetting. These insights underscore the importance of proactive risk management and collaboration among stakeholders to ensure data integrity and regulatory compliance in cloud environment.